Rapidly progressive IgA nephropathy with anti-myeloperoxidase antibodies benefits from immunosuppression - Allmaras, Eberhard; Nowack, R; Andrassy, Konrad; Waldherr, Rüdiger; Woude, Fokko J. van der; Ritz, Eberhard (Clinical nephrology, 1997)
Clinical observationsThree patients with previous pulmonary infections were recently admitted with rapidly progressive renal failure. Renal biopsy showed crescentic glomerulonephritis with deposits of IgA, C3c and C3d. Serology disclosed P-ANCA with high-titer anti-myeloperoxidase antibodies. Two out of three patients became dialysis dependent despite immunosuppression with methylprednisolone and cyclophosphamide. Renal function improved in both patients after 2 weeks and 9 months, respectively, permitting termination of hemodialysis. All patients benefited from immunosuppressive treatment which is currently still being continued.ConclusionThe data suggest that early immunosuppression is beneficial in patients presenting with crescentic rapidly progressive IgA GN and anti-myeloperoxidase antibodies, which may represent a novel subset of crescentic IgA GN associated with high-titer anti-myeloperoxidase antibodies constituting an overlap group between microscopic polyangiitis and IgA GN.